2002
DOI: 10.1074/jbc.m107313200
|View full text |Cite
|
Sign up to set email alerts
|

Gankyrin Is an Ankyrin-repeat Oncoprotein That Interacts with CDK4 Kinase and the S6 ATPase of the 26 S Proteasome

Abstract: A yeast two-hybrid screen with the human S6 (TBP7, RPT3) ATPase of the 26 S proteasome has identified gankyrin, a liver oncoprotein, as an interacting protein.Gankyrin interacts with both free and regulatory complex-associated S6 ATPase and is not stably associated with the 26 S particle. Deletional mutagenesis shows that the C-terminal 78 amino acids of the S6 ATPase are necessary and sufficient to mediate the interaction with gankyrin. Deletion of an orthologous gene in Saccharomyces cerevisiae suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 72 publications
7
97
1
1
Order By: Relevance
“…1A), except Rpn3, Rpn5, Rpn7, and Rpn12, which were not resolved, perhaps because of poor solubility of these proteins (13). We also confirmed the proteasome association of several known cofactors, including PA28 (27), Hsp70 (28), gankyrin (29), and Usp14/Ubp6 (28,30). In addition to these proteins, Txnl1, a thioredoxinlike protein implicated in endocytosis (31) and reactions to glucose deprivation (32), was consistently found in the proteasome preparations (Fig.…”
Section: Txnl1 Associates With 26 S Proteasomes-26 S Proteasomes Fromsupporting
confidence: 64%
“…1A), except Rpn3, Rpn5, Rpn7, and Rpn12, which were not resolved, perhaps because of poor solubility of these proteins (13). We also confirmed the proteasome association of several known cofactors, including PA28 (27), Hsp70 (28), gankyrin (29), and Usp14/Ubp6 (28,30). In addition to these proteins, Txnl1, a thioredoxinlike protein implicated in endocytosis (31) and reactions to glucose deprivation (32), was consistently found in the proteasome preparations (Fig.…”
Section: Txnl1 Associates With 26 S Proteasomes-26 S Proteasomes Fromsupporting
confidence: 64%
“…However, the role of gankyrin in cell cycle progression in ESCC is still unclear. Moreover, based on the studies on apoptotic growth factors that have suggested that G1/S stages of the cell cycle may be apoptotic insensitive stages 37 and that S6 ATPase-gankyrin-Rb-E2F1 interactions may control E2F1 stability in relation to the G1/S transition, 38 we demonstrated that the down-regulation of gankyrin expression inhibited proliferation in an ESCC cell line, inducing an accumulation of cells in the G1/S phase in vitro. Furthermore, we clearly demonstrated that the down-regulation of gankyrin inhibited tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For binding studies with radiolabelled subunits, equal amounts (9 lg) of GST or GST-a-subunit were immobilised onto (GSH)-Sepharose beads and processed as described [17]. Protein fractions were subjected to SDS-PAGE followed by Western blot analyses, Coomassie staining or phosphor-imager analyses (Fujifilm FLA-2000R).…”
Section: Expression Purification and Binding Analyses Of Recombinantmentioning
confidence: 99%
“…Strain SFY526 has only a lacZ reporter gene, but it is controlled by an intact GAL1 UAS and therefore can be expressed at $10Â the level obtained with the UAS G17-mer ðx3Þ promoter. For qualitative analysis of Y2H interactions, activity of the b-galactosidase reporter gene was assessed as described previously [17].…”
Section: The Yeast Two-hybrid Systemmentioning
confidence: 99%